THE EFFECT OF PROMOTION AND BRAND AWARENESS ON CUSTOMER SATISFACTION AND CUSTOMER LOYALTY IN ECOMMERCE SHOPEE - Novi Fitria Hermiati; Afifah Nur Rimadhani; Surya Bintarti; Daspar Daspar (Institute of Computer Science (IOCS), 2022)
This study aims to examine the effect of promotion on customer satisfaction and customer loyalty, and also to examine the effect of brand awareness on customer satisfaction and customer loyalty, as well as test customer satisfaction on customer loyalty on e-commerce shopee. The sampling method used in this research is probability sampling with purposive sampling technique. The number of samples used was 100 respondents. The population used in this study were students of Pelita Bangsa University Management Study Program class of 2018 who used ecommerce ShopeeThe data obtained was processed using smartPLS (Partial Least Square) software. The tests used are the first outer model analysis inner model analysis, and hypothesis testing. Findings from the structural model there are 4 proven hypotheses and 1 unproven hypothesis. The results of this study prove that the promotion variable has an effect on customer satisfaction, brand awareness has an effect on customer satisfaction, brand awareness has an effect on customer loyalty, and customer satisfaction has an effect on customer loyalty. However, promotion has no effect on customer loyalty.